(untitled) (Fiep Bulletin - online, 2012)
This case arose out of one of the most common concerns, especially by the elderly: Alzheimer’s disease. Interest focused on the identification and analysis of knowledge, prevention measures and the perception of older people about this that is one of the most stigmatized diseases. The significant growth of the elderly population is remarkable and with it an increase in elderly patients with Alzheimer’s disease. In the survey, we tried to know about the vision of elderly Alzheimer’s disease in a context that involves preventive aspects, meanings and social relations, that is, how they behave before this madness that directly affects people aged sixty and over age. The research aimed to identify differences in the vision of a group of elderly Alzheimer’s disease. The study was conducted in the Sports Center, located in the city of Caieiras, São Paulo. The subjects are part of a group that, among other activities, regular physical activity: twice a week. The statements of the subjects showed fear and total rejection of the disease. On the other hand, spirituality is identified as an effective defense mechanism against its manifestation. In addition to the regular sequence of physical activities, faith in God appears as a very effective way to prevent disease, both come at last, as important mechanisms to strengthen the body of the elderly.